Co-B catalyst and preparation method and application thereof

The Co-B catalyst prepared by one-step chemical reduction method solves the problems of complex preparation process and insufficient catalyst performance in the prior art, and achieves efficient hydrogen production by NaBH4 hydrolysis, and has good thermal stability and cycling performance.

CN119657145APending Publication Date: 2025-03-21GUANGDONG TECHN COLLEGE OF WATER RESOURCES & ELECTRIC ENG
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411423976.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-12
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

The existing Co-B catalyst has complex preparation process, low specific surface area, easy to coalesce and poor thermal stability, which limits its application in the hydrolysis of NaBH4 hydrogen.

Method used

By a one-step chemical reduction method, a Co-B catalyst with a larger pore size and specific surface area was prepared by oxidation reduction reaction of cobalt compound and NaBH4 in water or glycol solution.

Benefits of technology

High efficiency of catalyzing NaBH4 hydrolysis to produce hydrogen was achieved, the catalyst showed a significant catalytic rate at 45ºC, and maintained a high catalytic efficiency during multiple cycles.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119657145A_ABST
    Figure CN119657145A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of catalysts, and discloses a Co-B catalyst and a preparation method and application thereof. The cobalt boride catalyst is prepared by adopting a chemical reduction method, and the method comprises the following steps: dissolving a cobalt compound in water or ethylene glycol or a mixed solution consisting of water and ethylene glycol, and heating to a certain temperature to obtain a solution A; dissolving NaBH4 and NaOH in water or ethylene glycol or a mixed solution composed of water and ethylene glycol to obtain a solution B; under the stirring condition, dropwise adding the solution B into the solution A for reaction, and centrifuging, washing, drying and passivating the obtained product to obtain the Co-B catalyst. The preparation method is simple and convenient, the Co-B catalyst for catalyzing hydrolysis of NaBH4 to produce hydrogen is synthesized through a one-step chemical reduction method, the catalyst has a large pore diameter and a large specific surface area and shows good catalytic efficiency, and the release rate of catalyzing hydrolysis of NaBH4 at 45 DEG C is 2659.8 mL min <-1 > g <-1 >.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of catalysts, and in particular relates to a Co-B catalyst and a preparation method and application thereof. Background Art

[0002] Fossil fuels (such as coal, oil, natural gas, etc.) used in social production and life are non-renewable energy sources. At present, large-scale mining of fossil fuels will lead to the depletion of their resources. Therefore, there is an urgent need to find an environmentally friendly new energy material to replace fossil fuels in order to solve the energy crisis and reduce environmental pollution. Hydrogen energy, as a new energy carrier, is considered to be one of the most promising alternatives to fossil fuels and has broad development prospects. Therefore, how to prepare and store hydrogen in large quantities has become a hot topic in current research. The hydrogen production strategy of metal hydride hydrolysis reaction has received widespread global attention in recent years due to its safety, environmental protection, efficiency and controllability. Among metal hydrides, sodium borohydride (NaBH4) has attracted much attention due to its high hydrogen storage capacity.

[0003] NaBH4 can be stored in alkaline solution for a long time and can be taken out when hydrogen is needed. In fact, in order to achieve the hydrolysis of NaBH4, a suitable catalyst must be used. The catalysts currently studied can be divided into precious metal-based materials and non-precious metal-based materials. Although precious metals (such as platinum, rhodium, ruthenium, etc.) show good catalytic activity in catalytic hydrolysis, they have not yet been widely used in actual production and life due to their high cost and limited resources. Therefore, some non-precious metal catalysts, such as cobalt, nickel, copper, etc., have gradually been developed and used for the hydrolysis of NaBH4 solutions. In recent years, with the deepening of research, it has been found that Co-B catalysts with cobalt as the active center have good activity in catalyzing the hydrolysis of NaBH4 to produce hydrogen. For example, Saka et al. (SAKA C, KAYA M, BEKIROĞULLARI M. Spirulina Platensis microalgae strain modified with phosphoric acid as a novel support material for Co–B catalysts: Its application to hydrogen production [J]. Int J Hydrogen Energy, 2020, 45(4): 2872-83.) prepared a CoB catalyst supported by Spirulina microalgae treated with H3PO4, and modified the Spirulina microalgae strain into protons with H3PO4. Ruan et al. (RUAN J, WANG S, YANG F, et al. Hydrolysis of NaBH4 using carbonized melamine foam-supported cobalt borate composite catalyst for H2production [J]. Int J Electrochem Sci, 2024, 19(2): 100461.) used a static aging method to load a thick sheet of Co-MOF precursor onto CMF, and prepared a CMF-CoO composite material with a coral rod structure as a catalyst support. Subsequently, the CoB particles are uniformly loaded on the surface of CMF-CoO through a reduction reaction to obtain a CMF-CoO-CoB composite catalyst. However, there are still some shortcomings in the current related work, such as complicated preparation process, low specific surface area of ​​the synthesized catalyst, easy agglomeration and poor thermal stability. Therefore, in view of the above-mentioned shortcomings, a Co-B catalyst with good catalytic performance is prepared by a simple and convenient method, which has broad application prospects. Summary of the invention

[0004] In order to overcome the shortcomings and deficiencies of the prior art, the primary purpose of the present invention is to provide a method for preparing a Co-B catalyst.

[0005] Another object of the present invention is to provide a Co-B catalyst.

[0006] Another object of the present invention is to provide application of the above-mentioned Co-B catalyst in producing hydrogen by hydrolysis.

[0007] The purpose of the present invention is achieved through the following technical solutions: A method for preparing a Co-B catalyst comprises the following steps: (1) Dissolve the cobalt compound in water or ethylene glycol or a mixed solution of water and ethylene glycol, and heat to a certain temperature to obtain liquid A; (2) Dissolve NaBH4 and NaOH in water or ethylene glycol or a mixed solution of water and ethylene glycol to obtain solution B; (3) Under stirring conditions, droplets of liquid B are added to liquid A for redox reaction. The resulting product is centrifuged, washed, dried, and passivated to obtain a Co-B catalyst.

[0008] Preferably, the mass ratio of water to ethylene glycol in the mixed solution is 0.1:1~1:0.1.

[0009] Preferably, the heating in step (1) is heating to 80-100°C.

[0010] Preferably, the cobalt compound in step (1) is one of CoCl2·6H2O, Co(OAc)2·4H2O, CoSO4, CoCO3, and CoC2O4.

[0011] Preferably, the dropping speed is 5-15 g / min.

[0012] Preferably, the passivation is carried out in air at 0.1-1 Pa for 12-36 h.

[0013] A Co-B catalyst is prepared by the above method.

[0014] Preferably, the catalyst has a pore size of 10-800 nm and a specific surface area of ​​20-140 m 2 / g.

[0015] Application of the above Co-B catalyst in hydrogen production by hydrolysis of NaBH4.

[0016] Preferably, the temperature during the application is 25°C to 50°C.

[0017] Compared with the prior art, the present invention has the following advantages and beneficial effects: (1) The preparation method of the present invention is simple and convenient, and the Co-B catalyst for catalyzing the hydrolysis of NaBH4 to produce hydrogen is synthesized by a one-step chemical reduction method.

[0018] (2) The catalyst has both a large pore size and a large specific surface area, showing good catalytic efficiency. The appropriate temperature environment during the catalytic process can significantly improve the catalytic rate of the Co-B catalyst. The release rate of the Co-B catalyst for the hydrolysis of NaBH4 at 45°C is 2659.8 mL‧min -1 ‧g -1 .

[0019] (3) The catalyst prepared by the present invention can maintain a high catalytic efficiency after two catalytic cycles. After five cycles of testing, the hydrogen production rate dropped to 64.47% of the initial use. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 XRD patterns of Co-B catalysts: (a) is the XRD pattern of Co-B catalysts synthesized in different solvents; (b) is the XRD pattern of Co-B catalysts synthesized at different temperatures.

[0021] Figure 2 Figure 2 is the SEM image of Co-B catalyst synthesized by anhydrous A liquid at different water bath temperatures; (a) and (d) are the SEM images of catalyst A3; (b) and (e) are the SEM images of catalyst B3; (c) and (f) are the SEM images of catalyst C3.

[0022] Figure 3 This is the EDS image of catalyst C3, (a) EDS selected area; (b) O element; (c) Co element; (d) B element.

[0023] Figure 4 (a) Nitrogen adsorption / desorption isotherms of Co-B prepared with different solvent ratios; (b) Nitrogen adsorption / desorption isotherms of Co-B prepared with different reaction temperatures; (c) Pore size distribution of Co-B catalyst.

[0024] Figure 5 Performance diagram of different Co-B catalysts for NaBH4 hydrolysis to produce hydrogen, 5 (a) The effect of different temperatures on the Co-B catalyst catalyzing the hydrolysis of NaBH4 to produce hydrogen; (b) The effect of different A solvent ratios on the Co-B catalyst catalyzing the hydrolysis of NaBH4 to produce hydrogen; (c) The effect of different catalytic temperatures on the Co-B catalyst catalyzing the hydrolysis of NaBH4 to produce hydrogen; (d) The cyclic performance test of the Co-B catalyst. DETAILED DESCRIPTION

[0025] The present invention is further described in detail below in conjunction with specific embodiments, but the embodiments of the present invention are not limited thereto. For process parameters not particularly noted, conventional techniques may be used.

[0026] Sodium borohydride (NaBH4, analytical grade), sodium hydroxide (NaOH, analytical grade), cobalt chloride (CoCl2·6H2O, analytical grade), anhydrous ethanol (C2H5OH, analytical grade), and ethylene glycol (CH2OH2, analytical grade).

[0027] Example 1 3g CoCl2·6H2O was dissolved in 50g mixed solution of deionized water and ethylene glycol (H2O: CH2OH2=1:0), recorded as liquid A, and transferred to a three-necked flask, and then heated to 80 ºC in a water bath. 1.89g NaBH4 and 2g NaOH were dissolved in 50g mixed solution of deionized water and ethylene glycol (H2O: CH2OH2=1:0), recorded as liquid B, and liquid B was titrated into liquid A at a rate of 10 g / min at a fixed stirring frequency. After the reaction, the synthesized catalyst was centrifuged and then ultrasonically cleaned alternately with deionized water and anhydrous ethanol until there was no obvious impurity. The cleaned sample was dried in a vacuum drying oven at 60ºC for 12 h, and then placed in 0.1 Pa air for passivation for 24 h. The dried Co-B catalyst was ground into powder and packaged for storage. The catalyst was recorded as A1.

[0028] Example 2 Different from Example 1, 3 g of CoCl2·6H2O was dissolved in 50 g of a mixed solution of deionized water and ethylene glycol (H2O : CH2OH2=1:1), and 1.89 g of NaBH4 and 2 g of NaOH were dissolved in 50 g of a mixed solution of deionized water and ethylene glycol (H2O : CH2OH2=1:1). The resulting catalyst was recorded as A2.

[0029] Example 3 Different from Example 1, 3 g of CoCl2·6H2O was dissolved in 50 g of a mixed solution consisting of deionized water and ethylene glycol (H2O : CH2OH2=0:1), and 1.89 g of NaBH4 and 2 g of NaOH were dissolved in 50 g of a mixed solution consisting of deionized water and ethylene glycol (H2O : CH2OH2=0:1). The resulting catalyst was recorded as A3.

[0030] Example 4 The difference from Example 1 is that the temperature is heated to 90°C and the catalyst is recorded as B1.

[0031] Example 5 The difference from Example 2 is that the temperature is heated to 90°C and the catalyst is recorded as B2.

[0032] Example 6 The difference from Example 3 is that the temperature is heated to 90°C and the catalyst is recorded as B3.

[0033] Example 7 The difference from Example 1 is that the temperature is heated to 100 ºC and the catalyst is recorded as C1.

[0034] Example 8 The difference from Example 2 is that the catalyst is heated to 100°C and is recorded as C2.

[0035] Example 9 The difference from Example 3 is that the catalyst is heated to 100°C and is recorded as C3.

[0036] Test Case The Co-B catalysts prepared in Examples 1 to 9 were characterized by using a D / Max-Uitimal V X-ray diffractometer (XRD) from 10° to 80° at 7° min -1 The Co-B catalyst was analyzed at a scanning speed of . The microstructure of the Co-B catalyst was observed using a SU 8010 scanning electron microscope (SEM). The elemental composition of the catalyst was determined by an energy dispersive spectrometer (EDS), and the test results are as follows: (1) XRD analysis of Co-B catalyst In order to determine the composition of the synthesized catalyst, XRD test was carried out on it. Figure 1 is the XRD pattern of Co-B catalyst. Figure 1 (a) It can be seen that under different solvent environments, the synthesized Co-B catalyst does not form a diffraction peak, indicating that the structure of the catalyst is an amorphous structure. It can be observed that under different H2O and CH2OH2 solubility ratios, the XRD pattern of the synthesized Co-B catalyst changes very little, indicating that under different H2O and CH2OH2 solubility ratios, the synthesized catalyst does not undergo a phase transition. Figure 1 (b) is the XRD spectrum of the Co-B catalyst synthesized at different water bath temperatures. Obviously, the synthesized Co-B catalyst has an amorphous structure and the phase does not change with the change of the water bath temperature.

[0037] (2) SEM and EDS characterization analysis of Co-B catalyst Characterization of the microstructure morphology and element distribution of the catalyst is helpful to further understand the catalytic mechanism of the catalyst. Figure 2 The SEM images of the Co-B catalyst synthesized by anhydrous liquid A at different water bath temperatures are shown in Figure 2. Figure 2 (a) Figure 2 (b) and Figure 2 Comparison with (c) shows that the Co-B-loaded particles synthesized at 100 ºC are smaller and denser, with an overall size between 1-4 μm. Figure 2 (d) Figure 2 (e) and Figure 2 (f) SEM images of Co-B synthesized at 80 ºC, 90 ºC and 100 ºC at higher magnifications, showing that some smaller particles with a size of 100-200 nm are attached to the surface of the large particles of the synthesized Co-B catalyst. This means that the Co-B catalyst synthesized at 100 ºC may have a larger specific surface area and thus better catalytic performance.

[0038] Figure 3 The EDS image of the Co-B catalyst (C3) synthesized from anhydrous A solution at 100 ºC shows that Co and B are evenly distributed in the Co-B catalyst. Combined with the XRD analysis results, this indicates that the Co-B catalyst was successfully synthesized. The presence of O indicates that the surface of the catalyst may have been partially oxidized.

[0039] (3) BET analysis of Co-B catalyst The pore size and specific surface area of ​​the catalyst are the key factors affecting its catalytic performance. Figure 4 Table 1 shows the pore size and specific surface area information of the synthesized Co-B series catalysts. Figure 4 (a) and Figure 4 (b) Nitrogen adsorption / desorption isotherms of the synthesized Co-B catalysts at different solvent ratios and reaction temperatures. Figure 4 (a) and Figure 4 As shown in (b), the isotherm curves of C1, C2, C3, A1 and B1 catalysts all have hysteresis loops. C1 and C2 make the isotherm curves convex and have inflection points at lower pressures, and the latter part of the curve is convex here. The physical adsorption curves of this series of Co-B catalysts conform to the IV curve in the IUPAC classification, indicating that this series of Co-B catalysts has a large number of mesoporous structures. From Table 1, it can be seen that the Co-B catalysts synthesized at 90 ºC all show the smallest specific surface area, with a value of 20-30m 2 / g, while the Co-B catalyst synthesized at 100 ºC has a larger specific surface area, with a value of 80-140m 2 / g, proving that the Co-B catalyst synthesized at 100 ºC has a larger specific surface area, resulting in better catalytic effect. The catalytic effect of the catalyst is also affected by the pore size. Figure 4(c) and Table 1 show that sample B2 has the largest pore size. It is observed that the pore size has no direct relationship with the reaction temperature and solvent ratio. Specific surface area and pore size are both key factors affecting the catalytic performance of the catalyst. Although sample B2 has the largest pore size, its specific surface area is too small. Although sample C1 has the largest specific surface area, its pore size is much smaller than other samples. Therefore, it can be inferred that the two samples will not have the best hydrogen production performance. The pore size of C3 is about the second largest among many samples, and its specific surface area is slightly smaller than that of sample C1. Therefore, it can be inferred that sample C3 may have better hydrogen production performance.

[0040] Table 1 Surface area analysis of Co-B materials Application example: Study on the catalytic activity of Co-B catalyst Figure 5 The performance diagram of different Co-B catalysts for NaBH4 hydrolysis to produce hydrogen. In order to explore the effect of synthesis temperature on the dehydrogenation performance of Co-B catalysts, 0.005 g of A3, B3 and C3 catalysts were added at 25 ºC for hydrolysis tests. The hydrolysis test conditions are as follows: 0.005 g catalyst, 0.4 g NaBH4, 0.4 g NaOH, 4.2 g H2O, a total of 5 g solution, i.e. 8% NaBH4 + 8% NaOH + 84% H2O, and the reaction temperature is 30°C.

[0041] Figure 5 (a) is the catalytic hydrolysis performance diagram of Co-B catalyst at different synthesis temperatures. It can be seen from the figure that A3, B3 and C 3 The rate of hydrogen production by catalytic hydrolysis of NaBH4 was 420.7 mL‧min -1 ‧g -1 、475.4 mL‧min -1 ‧g -1 and 503.9 mL‧min -1 ‧g -1 As the temperature of the synthesized catalyst increases, the hydrogen production rate of NaBH4 also increases. Combined with the SEM analysis results, it can be seen that the Co-B catalyst synthesized at 100 ºC has a larger specific surface area and thus has a better catalytic efficiency.

[0042] Figure 5 (b) is a test diagram of the performance of NaBH4 hydrolysis catalyzed by Co-B catalysts synthesized under different solvent ratios. As shown in the figure, the rates of hydrogen production by NaBH4 hydrolysis catalyzed by C1, C2 and C3 are 267.2 mL‧min -1 ‧g -1 、286.2 mL‧min -1‧g -1 and 503.9 mL‧min -1 ‧g -1 Obviously, the rate of hydrogen production from the hydrolysis of NaBH4 catalyzed by the Co-B catalyst increases with the decrease of H2O in solvent A. The Co-B catalyst synthesized when H2O : CH2OH2 = 0 : 1 has the best catalytic efficiency. Combined with the analysis of the pore size and specific surface area of ​​the Co-B catalyst, it can be seen that the simultaneous presence of large pore size and large specific surface area can make the catalyst have better catalytic performance.

[0043] Figure 5 (c) is a test chart of the catalytic performance of Co-B catalyst at different temperatures. The test conditions are as follows: 0.005g catalyst, 0.4g NaBH4, 0.4g NaOH, 4.2g H2O, 5g solution, i.e. 8% NaBH4+8% NaOH +84% H2O, reaction temperature is 30℃, 35℃, 40℃, 45℃, 50℃. It can be observed that the time taken for the hydrolysis rate of NaBH4 to decrease from 30 ºC to 45 ºC, indicating that the catalytic rate is increasing. As the temperature rises to 50 ºC, the catalytic rate is 2694.1mL‧min -1 ‧g -1 , compared to the catalytic rate of 2659.8 mL‧min at 45 ºC -1 ‧g -1 The catalytic rate of the Co-B catalyst at 50 ºC did not change significantly. The catalytic rate of the Co-B catalyst at 50 ºC is almost 5 times the catalytic efficiency of C3, indicating that the appropriate catalytic temperature can maximize the catalytic effect of the Co-B catalyst. Figure 5(d) is a test diagram of the catalytic performance of the Co-B catalyst under different cycle conditions. The test conditions are as follows: 0.005g catalyst, 0.4g NaBH, 0.4g NaOH, 4.2g H2O, and a total of 5g solution, i.e. 8% NaBH + 8% NaOH + 84% H2O. The Co-B catalyst is continuously separated and recovered from the solution by a magnetic stirrer for repeated use. Figure 5 (d) It can be found that the catalytic activity of the synthesized Co-B catalyst gradually decreases with the increase of the number of cycles. After two cycles, the catalytic efficiency can still be maintained at a high level. After five cycles, the hydrogen production rate dropped to 64.47% of the initial use. This may be due to the fact that the Co-B catalyst generates more and more NaBO2 byproducts after multiple cycles, and the catalyst partially agglomerates, and part of the Co-B catalyst is lost during the reuse process.

[0044] The present invention regulates the temperature and A solvent ratio of the synthesized catalyst and studies the influence of the temperature and A solvent ratio on the specific surface area and pore size of the Co-B catalyst. When the Co-B catalyst is synthesized at different temperatures, its physical phase does not change, and the catalyst synthesized at a synthesis temperature of 100 ºC has a larger specific surface area. The pore size of the Co-B catalyst is not regulated by the solvent ratio. Finally, the Co-B catalyst synthesized at 100 ºC and an A solvent ratio of H2O: CH2OH2=0:1 has the maximum hydrogen production rate when catalyzing the hydrolysis of NaBH4.

[0045] Through the analysis of SEM, pore size and specific surface area, it can be seen that the catalytic activity of the Co-B catalyst is affected by both the pore size and the specific surface area. Having a large specific surface area and pore size alone cannot improve the catalytic performance of the catalyst. Only when both are larger, the Co-B catalyst has better catalytic activity.

[0046] As the temperature increases during the process of catalyzing the hydrolysis of NaBH4 to produce hydrogen by the Co-B catalyst, the catalytic performance of the catalyst is significantly improved. When the temperature exceeds 45 ºC, the catalytic performance of the Co-B catalyst has no obvious improvement, indicating that the appropriate catalytic temperature can maximize the catalytic performance of the Co-B catalyst.

[0047] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.

Claims

1. A method for preparing a Co-B catalyst, characterized in that: The following steps are involved: (1) Dissolve the cobalt compound in water or ethylene glycol or a mixed solution of water and ethylene glycol, and heat to a certain temperature to obtain liquid A; (2) Dissolve NaBH4 and NaOH in water or ethylene glycol or a mixed solution of water and ethylene glycol to obtain solution B; (3) Under stirring conditions, droplets of liquid B are added to liquid A for redox reaction. The resulting product is centrifuged, washed, dried, and passivated to obtain a Co-B catalyst.

2. The method for preparing the Co-B catalyst according to claim 1, characterized in that: The mass ratio of water to ethylene glycol in the mixed solution is 0.1:1~1:0.

1.

3. The method for preparing the Co-B catalyst according to claim 1, characterized in that: The heating in step (1) is heating to 80-100°C.

4. The method for preparing the Co-B catalyst according to claim 1, characterized in that: The cobalt compound in step (1) is one of CoCl2·6H2O, Co(OAc)2·4H2O, CoSO4, CoCO3, and CoC2O4.

5. The method for preparing the Co-B catalyst according to any one of claims 1 to 4, characterized in that: The dropping speed is 5-15 g / min.

6. The method for preparing the Co-B catalyst according to claim 5, characterized in that: The passivation is carried out in an air atmosphere of 0.1-1 Pa for 12-36 hours.

7. A Co-B catalyst, characterized in that The method is prepared by any one of claims 1 to 6.

8. The Co-B catalyst according to claim 7, characterized in that The catalyst has a pore size of 10-800 nm and a specific surface area of ​​20-140 m 2 / g.

9. Use of the Co-B catalyst according to claim 7 or 8 in producing hydrogen by hydrolysis of NaBH4.

10. The use according to claim 9, characterized in that: The temperature during the application is 25°C to 50°C.